Effects of Work-Life Balance Training Programs on Employee Job Motivation: A Quantitative Analysis - Seyed Alitabar, Seyed Hadi (KMAN Counseling & Psychology Nexus, 2023)
This study aims to evaluate the efficacy of work-life balance training on improving job motivation among employees, utilizing a controlled experimental design to assess changes over time and sustainment of these changes post-intervention. A total of 40 participants were divided equally into experimental and control groups. The experimental group received work-life balance training, while the control group did not. Job motivation was measured for both groups at three time points: pre-test, post-test, and follow-up (three months post-intervention), using standardized questionnaires. Descriptive statistics and Analysis of Variance (ANOVA) with repeated measurements, followed by Bonferroni Post-Hoc tests, were employed to analyze the data. The experimental group showed a significant increase in job motivation from the pre-test (M=92.40, SD=20.10) to the post-test (M=110.73, SD=22.15), which was sustained at the follow-up (M=110.09, SD=22.49). In contrast, the control group's job motivation scores remained stable and showed no significant improvement. ANOVA results confirmed significant effects of time, group, and time × group interaction on job motivation, indicating the positive impact of the work-life balance training. Work-life balance training significantly improves job motivation among employees, with effects that are maintained over a medium-term period. This suggests that such interventions can be an effective strategy for organizations looking to enhance employee well-being and job motivation.